Anandamide Exerts a Differential Effect on Human Placenta Before and After the Onset of Labor - Accialini, Paula; Abán, Cyntia; Etcheverry, Tomás; Negri Malbrán, Mercedes; Leguizamón, Gustavo; Herlax, Vanesa; Maté, Sabina; Farina, Mariana (Frontiers in Physiology, 2021)
The onset of labour involves the action of multiple factors and recent reports have postulated the endocannabinoid system as a new regulator of this process. Our objective was to study the role of anandamide, one of the main endocannabinoids, on the regulation of placental molecules that contribute to the onset of labor at term. Placental samples were obtained from patients with labouring vaginal deliveries and from non-labouring elective cesarean sections. Vaginal delivery placentas produced higher prostaglandins levels than cesarean section samples. Besides, no differences were observed in NOS basal activity between groups. Incubation of vaginal delivery placentas with anandamide increased prostaglandins concentration and decreased NOS activity. Antagonism of type-1cannabinoid receptor (CB1) did not alter the effect observed on NOS activity. Conversely, incubation of cesarean section placentas with anandamide reduced prostaglandins levels and enhanced NOS activity, the latter involving the participation of CB1. Furthermore, we observed a differential expression of the main components of the endocannabinoid system between placental samples, being the change in CB1 localization the most relevant finding. Our results suggest that anandamide acts as a modulator of the signals that regulate labour, exerting differential actions depending on CB1 localization in labouring or non-labouring term placentas.